Two Cheers for RRBM, Pasteur's Quadrant, and an Application of RRBM to the Commercialization of Science and Technology Transfer. (27th March 2022) - Siegel, Donald S.
Abstract: In this essay, I present my perspective on the Responsible Research in Business and Management (RRBM) movement, which is a timely and important initiative. I connect RRBM to previous debates about the nature and value of basic research and the role of key institutions, such as universities and federal/national labs, and show how RRBM is consistent with 'Pasteur's Quadrant' of 'use‐inspired basic research'. Next, I demonstrate how RRBM principles can be applied to the study of the commercialization of science and technology transfer. My only reservations about RRBM are its overemphasis on social problems, the opportunity costs associated with deflecting attention away from more pressing managerial problems, and concern that we need to be mindful of work and expertise in other disciplines that more directly address public policy issues.